Review Capital Structure and Good Corporate Governance Toward Islamic Banking Performance In Indonesia - Ridwansyah Ridwansyah; Anip Dwi Saputro (Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
This study aims to review capital structure and the implementation of Good Corporate Governance (GCG) toward Islamic Banking performance in Indonesia. The research results can be depicted that the capital structure and corporate governance has been running well. Slowing Islamic banking is dominated by external economic slowdown that occurred in Indonesia. However, main sources of Islamic bank capital are core capital (core capital) which comes from the owners of the banks and quasi-equity. When the world financial crisis and the shareholders take their share of Islamic banks then certainly slowing global political factor because it is Identic with the capitalist and the capital structure of Islamic banks is still not much yet as the conventional banking which is inherently present in this global world.